A qualitative exploration of experiences of overweight young and older adults: An application of the integrated behaviour model - Robertson, A.; Mullan, Barbara; Todd, J. (Elsevier BV, 2014)
While rates of obesity continue to increase, weight-loss interventions to date have not been hugely successful. The purpose of this study was to explore the specific factors that are relevant to weight control in overweight and obese young adults compared to older adults, within the context of the theory of planned behaviour (TPB). A qualitative methodology with purposive sampling was used. Semi-structured interviews were conducted with 23 young adults and older adults who were currently overweight or obese. The research was informed by thematic analysis. A mixed deductive–inductive approach that was structured around but not limited to TPB constructs was applied. Themes mapped onto the TPB behaviour well, with additional themes of motivation, and knowledge and experience emerging. Differences across groups included motivators to weight loss (e.g. appearance and confidence for young adults, health for older adults), importance of social influences, and perceptions of control (e.g. availability and cost for young adults, age and energy for older adults). Similarities across groups included attitudes towards being overweight and losing weight, and the value of preparation and establishment of a healthy routine. Finally, across both groups, knowledge and confidence in ability to lose weight appeared adequate, despite failed attempts to do so. The different experiences identified for younger and older adults can be used to inform future tailored weight-loss interventions that are relevant to these age groups, and the TPB could provide a useful framework. Additional intervention strategies, such as improving behavioural routine and improving self-regulation also warrant further investigation.